2011
DOI: 10.1063/1.3660216
|View full text |Cite
|
Sign up to set email alerts
|

Soliton states in mesoscopic two-band-superconducting cylinders

Abstract: In the framework of the Ginzburg-Landau approach, we present a self-consistent theory of specific soliton states in mesoscopic (thin-walled) two-band-superconducting cylinders in external parallel magnetic fields. Such states arise in the presence of "Josephson-type" interband coupling, when phase winding numbers are different for each component of the superconducting order parameter. We evaluate the Gibbs free energy of the sysyem up to second-order terms in a certain dimensionless parameter ε ≈ Lm L k ≪ 1, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…In this situation, the formation of a chiral domain played a similar role as a soliton. Kuplevakhsky, Omelyanchouk and Yerin theoretically demonstrated that the phase shift was caused by the formation of a soliton in the ring of an intrinsic multiband superconductor [6]. This provides a plausible explanation for our experimental results.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…In this situation, the formation of a chiral domain played a similar role as a soliton. Kuplevakhsky, Omelyanchouk and Yerin theoretically demonstrated that the phase shift was caused by the formation of a soliton in the ring of an intrinsic multiband superconductor [6]. This provides a plausible explanation for our experimental results.…”
Section: Introductionsupporting
confidence: 52%
“…[4] Moler and co-workers reported such an obstruction in a mimic multi-band superconductor composed of an AlO x insulating layer sandwiched between two Al layers with a two component function, making them bilayers [5]. Kuplevakhsky, Omelyanchouk and Yerin suggested that this obstruction is expected in intrinsic multiband superconductors [6]. Current superconducting electronics and devices are based on a single order parameter scheme.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…From the theoretical viewpoint, a variety of non-trivial phenomena has been proposed (e.g., topological phase soliton [7,8], odd-frequency pairing [9], multiple Leggett mode [10], hidden criticality [11], stable Sarma phase [12], and Lifshitz transitions with resonance effects and amplification of the critical temperature [13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Kupulevaksky and coworkers examined 18 this soliton state in mesoscopic thin-walled cylinders in external magnetic fields by using the Ginzberg-Landau approach,. Tanaka and coworkers suggested 19 that interesting excitations, including a phase domain surrounded by the i-soliton wall, can arise in two dimensions (i.e., D=2) since an i-soliton may be considered as a D-1 dimensional quantum phase dislocation.…”
mentioning
confidence: 99%